Pre-emptive immunotherapy for clearance of molecular disease in childhood acute lymphoblastic leukemia after transplantation - Rettinger, Eva; Dürken, Matthias (Biology of blood and marrow transplantation, 2017)
Monitoring of minimal residual disease (MRD) or chimerism may help guide pre-emptive immunotherapy (IT) with a view to preventing relapse in childhood acute lymphoblastic leukemia (ALL) after transplantation. Patients with ALL who consecutively underwent transplantation in Frankfurt/Main, Germany between January 1, 2005 and July 1, 2014 were included in this retrospective study. Chimerism monitoring was performed in all, and MRD assessment was performed in 58 of 89 patients. IT was guided in 19 of 24 patients with mixed chimerism (MC) and MRD and by MRD only in another 4 patients with complete chimerism (CC). The 3-year probabilities of event-free survival (EFS) were .69 ± .06 for the cohort without IT and .69 ± .10 for IT patients. Incidences of relapse (CIR) and treatment-related mortality (CITRM) were equally distributed between both cohorts (without IT: 3-year CIR, .21 ± .05, 3-year CITRM, .10 ± .04; IT patients: 3-year CIR, .18 ± .09, 3-year CITRM .13 ± .07). Accordingly, 3-year EFS and 3-year CIR were similar in CC and MC patients with IT, whereas MC patients without IT experienced relapse. IT was neither associated with an enhanced immune recovery nor an increased risk for acute graft-versus-host disease. Relapse prevention by IT in patients at risk may lead to the same favorable outcome as found in CC and MRD-negative-patients. This underlines the importance of excellent MRD and chimerism monitoring after transplantation as the basis for IT to improve survival in childhood ALL.